PENERAPAN METODE OBJECTIVE AND KEY RESULTS PADA STARTUP KEENANSUPERCAR PLATFORM JASA PENYEWAAN MOBIL MEWAH DI BALI - Ardian Nugraha Harisma Sumardana; Helmy Syah Alam; Tiawan (Jurnal Informatika Teknologi dan Sains (Jinteks), 2023)
Along with the rapid advancement of technology in this era of globalization, causing influence in various aspects of life, especially in the field of technology is increasing. Technology is used as a medium to achieve and pursue profit goals both in terms of sales, transactions, finance or services, for example startups. Various companies with new innovations are born, especially in the field of technology, and startups are often discussed by many people [1]. Keenansupercar is a startup that takes part in the transportation aspect, namely car rental that focuses on luxury cars. Keenansupercar is present as a car rental service platform that makes it easier for car renters to get information about the cars they want to rent in Bali. The problem faced by the Keenansupercar startup is that there is no business evaluation for achieving targets in the near future at the Keenansupercar startup, so that the achievement results are not in accordance with the target desired by the Keenansupercar startup. Therefore, the author makes a short-term business evaluation using the Objective and Key Results (OKR) method so that Keenansupercar startups can be more sensitive and responsive to changes and make Keenansupercar startups achieve the desired targets.